BUSINESS PROCESS FLEXIBILITY OF THE UKRAINIAN FOREST SECTOR: MANAGEMENT, ASSESSMENT AND STRATEGIC DIRECTIONS OF CHANGES (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article deals with the improvement of the system managing the forest sector business processes based onsome flexibility. Some flexibility significance of business processes carrying out by entities in the current economicenvironment has been confirmed. The flexibility of the business processes in the forest sector has been proved as a coredriver of its effective functioning. Moreover, it ensures the production mobility with changes of customer needs. Theown interpretation of the concept of "flexibility" has been given, as well as the flexibility assessment technique ofbusiness processes has been improved and tried out in business processes of the forest sector. The control system hasbeen studied as it is based on the implementation of industrial strategies taking into account the flexibility of anyproduction activities.
Keywords: flexibility, management of flexibility of production activities, management of flexibility, forest sector, industrial strategy.